Adaptive Management for International Development Programs - Loveridge, Donna (Australasian Evaluation Society Conference, 2007)
Capacity development, that is “the process whereby people, organisations and society as a whole unleash, strengthen, create, adapt and maintain capacity over time” (OECD 2005) has been a key aim of international aid programs. However, capacity development efforts have not met with resounding success despite approximately 25%, or USD15 billion a year, being spent by donors in recent years on technical assistance1 which has predominantly been aimed at developing capacity. A 1998 review by the World Bank (World Bank 1998) found that the success rate for capacity development efforts was between 30 – 40%. The Commission for Africa (2005) noted in 2005 that achievements were below expectations. The OECD (2007) sees capacity development as being one of the areas which are least responsive to development assistance and therefore one of the greatest challenges. This paper proposes that development practitioners and donors could benefit from taking an evaluative inquiry-type of approach to the design, implementation and monitoring and evaluation of capacity development programs. An alternative approach, “adaptive management”, is proposed. Adaptive management moves away from a rational linear A + B = C approach to capacity development towards constructing and testing theories of change2 for knowledge generation, adaptation and program improvement.

Agile Software Development: Adaptive Systems Principles and Best Practices - Meso, Peter; Jain, Radhika (Information Systems Management, 2006)
Today's environments of increasing business change require software development methodologies that are more adaptable. This article examines how complex adaptive systems (CAS) theory can be used to increase our understanding of how agile software development practices can be used to develop this capability. A mapping of agile practices to CAS principles and three dimensions (product, process, and people) results in several recommendations for “best practices” in systems development.
Keywords: IMPORTANT

Complexity Leadership Theory: An Interactive Perspective on Leading in Complex Adaptive Systems - Lichtenstein, Uhl-Bien; Schreiber, Orton; Lichtenstein, Benyamin; Uhl-Bien, Mary; Marion, Russ; Seers, Anson; Orton, James Douglas; Schreiber, Craig (Emergence, 2006)
Traditional, hierarchical views of leadership are less and less useful given the complexities of our modern world. Leadership theory must transition to new perspec-tives that account for the complex adaptive needs of organizations. In this paper, we propose that leadership (as opposed to leaders) can be seen as a complex dynamic process that emerges in the interactive "spaces between" people and ideas. That is, leadership is a dynamic that transcends the capabilities of individuals alone; it is the product of interaction, tension, and exchange rules governing changes in per-ceptions and understanding. We label this a dynamic of adaptive leadership, and we show how this dynamic provides important insights about the nature of leadership and its outcomes in organizational fields. We define a leadership event as a perceived segment of action whose meaning is created by the interactions of actors involved in producing it, and we present a set of innovative methods for capturing and analyzing these contextually driven processes. We provide theoretical and practical implications of these ideas for organizational behavior and organization and management theory.

The high cost of accurate knowledge - Sutcliffe, Kathleen M.; Weber, Klaus (Harvard Business Review, 2003)
Many business thinkers believe it's the role of senior managers to scan the external environment to monitor contingencies and constraints, and to use that precise knowledge to modify the company's strategy and design. As these thinkers see it, managers need accurate and abundant information to carry out that role. According to that logic, it makes sense to invest heavily in systems for collecting and organizing competitive information. Another school of pundits contends that, since today's complex information often isn't precise anyway, it's not worth going overboard with such investments. In other words, it's not the accuracy and abundance of information that should matter most to top executives--rather, it's how that information is interpreted. After all, the role of senior managers isn't just to make decisions; it's to set direction and motivate others in the face of ambiguities and conflicting demands. Top executives must interpret information and communicate those interpretations--they must manage meaning more than they must manage information. So which of these competing views is the right one? Research conducted by academics Sutcliffe and Weber found that how accurate senior executives are about their competitive environments is indeed less important for strategy and corresponding organizational changes than the way in which they interpret information about their environments. Investments in shaping those interpretations, therefore, may create a more durable competitive advantage than investments in obtaining and organizing more information. And what kinds of interpretations are most closely linked with high performance? Their research suggests that high performers respond positively to opportunities, yet they aren't overconfident in their abilities to take advantage of those opportunities.
Keywords: Administrative Personnel; Data Collection; Decision Making, Organizational; Economic Competition; Information Management; Investments; Marketing; Organizational Innovation; United States

Good Enough Governance Revisited - Grindle, Merilee S. (Development Policy Review, 2007)
The concept of good enough governance provides a platform for questioning the long menu of institutional changes and capacity-building initiatives currently deemed important (or essential) for development. Nevertheless, it falls short of being a tool to explore what, specifically, needs to be done in any real world context. Thus, as argued by the author in 2004, given the limited resources of money, time, knowledge, and human and organisational capacities, practitioners are correct in searching for the best ways to move towards better governance in a particular country context. This article suggests that the feasibility of particular interventions can be assessed by analysing the context for change and the implications of the content of the intervention being considered.

Planners versus Searchers in Foreign Aid - Easterly, William (Asian Development Review, 2006)
Only for the recipients of foreign aid is something akin to central planning seen as a way to achieve prosperity. The end of poverty is achieved with free markets and democracy—where decentralized “searchers” look for ways to meet individual needs—not Poverty Reduction Strategy Papers (PRSPs) to achieve Millennium Development Goals (MDGs). The PRSPs and MDGs create lots of bureaucracy but hold no one specific agency in foreign aid accountable for any one specific task. Planners in foreign aid use the old failed models of the past—the “Financing Gap”, the “poverty trap”, the government-to-government aid model; and the “expenditures = outcomes” mentality. Searchers in foreign aid would imitate the feedback and accountability of markets and democracy to provide goods and services to individuals until homegrown markets and democracy end poverty in the society as a whole. An example of the more promising “searchers” approach in foreign aid is 2006 Nobel Peace Laureate Mohammad Yunus and Grameen Bank.

Donors' Learning Difficulties: Results, Relationships and Responsibilities - Eyben, Rosalind (IDS Bulletin, 2005)